Modelling the potential of genetic control of malaria mosquitoes at national scale - North, Ace R. (BMC Biol, 2019)
BACKGROUND: The persistence of malaria in large parts of sub-Saharan Africa has motivated the development of novel tools to complement existing control programmes, including gene-drive technologies to modify mosquito vector populations. Here, we use a stochastic simulation model to explore the potential of using a driving-Y chromosome to suppress vector populations in a 10(6) km(2) area of West Africa including all of Burkina Faso. RESULTS: The consequence of driving-Y introductions is predicted to vary across the landscape, causing elimination of the target species in some regions and suppression in others. We explore how this variation is determined by environmental conditions, mosquito behaviour, and the properties of the gene-drive. Seasonality is particularly important, and we find population elimination is more likely in regions with mild dry seasons whereas suppression is more likely in regions with strong seasonality. CONCLUSIONS: Despite the spatial heterogeneity, we suggest that repeated introductions of modified mosquitoes over a few years into a small fraction of human settlements may be sufficient to substantially reduce the overall number of mosquitoes across the entire geographic area. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12915-019-0645-5) contains supplementary material, which is available to authorized users.